Determinantes do desempenho discente no ENADE em cursos de Ciências Contábeis - Ferreira, Mônica Aparecida (2015)
Currently, the accounting education has undergone significant changes, such as significant growth in the number of Accounting courses and the consequent increase in the number of vacancies offered, as well as changes in accounting standards in Brazil (Miranda, 2011). In this scenario, is faced with a performance history obtained by the students in Accounting from the Provão to the ENADE 2012, not very favorable. According to Santos (2012), in Provão 2002 and 2003, the students recorded an average of 32.0 (range 0-100) and the ENADE 2006 an average of 33.90. ENADE in 2009, the average was 39.9 and in 2012 34.5 (INEP, 2014). Thus, the general objective of this study was to identify the significant variables in ENADE 2012 result of explanation in Accounting. The guiding theory was the educational production function. For this research we selected a sample of 44 370 students of Accounting (77% of the population) who underwent ENADE in 2012. First held descriptive statistics of the variables, after we observed the Hierarchical Linear Model to analyze the effect of each variable on academic performance. The results show that variables of the \"Level Student\" that were significant in the performance of explanation were: gender, marital status, ethnicity, income, scholarship, way ticket, mother\'s education, secondary education school (public or private), type of high school (traditional or vocational), number of books, hours studied, undergraduate research participation, participation monitoring, participation outreach activities. And at Level Institution: administrative category of IES, region, number of graduates participants ENADE, entrants note (ESMS), percentage of teachers, infrastructure percentage, percentage didactic-pedagogical organization. It is considered the greatest contribution the fact that this work point out that the characteristics and attitudes of the students are the most responsible (90%) to determine the academic performance and that only 10% or so, shall be borne by institutional variables (teacher + institution )